1976
DOI: 10.1111/j.1365-2133.1976.tb07031.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial flora in psoriasis

Abstract: The aerobic bacterial flora of psoriatic plaques, uninvolved skin and the anterior nares of forty psoriatic patients was studied. The incidence od Staphylococcus aureus was 30% in the anterior nares, 20% on the plaques and 13% on the uninvolved skin. S. aureus counts were 3 x 10(2)/cm2 on the plaques and 1-5 x 10/cm2 on the normal skin. The total bacterial counts were also higher on plaques (7-9 x 10(3)/cm2) than on normal skin (3-0 x 10(3)/cm2). The incidence of lipophilic diphtheroids was significantly lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 12 publications
0
30
1
Order By: Relevance
“…The percentage of patients carrying S. aureus on psoriatic plaques was found to be 30% by ALY et al (1976). This is an intermediate between previous estimates of 50% and 26%, but certainly higher than the carriage rate in their control population.…”
Section: Psoriasiscontrasting
confidence: 59%
“…The percentage of patients carrying S. aureus on psoriatic plaques was found to be 30% by ALY et al (1976). This is an intermediate between previous estimates of 50% and 26%, but certainly higher than the carriage rate in their control population.…”
Section: Psoriasiscontrasting
confidence: 59%
“…Our results demonstrated no down‐regulation of TGF‐β1 in psoriasis compared to normal skin with a significant positive correlation between levels of TGF‐β1 in psoriatic plaques and serum, suggesting that the mechanisms for TGF‐β1 production and release in both these compartments may be related. The discrepancy in reported results among investigators may be explained by: (a) in psoriasis, TGF‐β1–related lack of growth regulation could be either due to down regulation of TGF‐β1 expression in psoriatic skin and/or down regulation of TGF‐β1 receptors in the skin; 8,16 (b) TGF‐β1 is primarily located in the stratum corneum and the granular layer of epidermis, the latter is diminished in older lesions of psoriasis 17 thus lesion's age may be an important determinant factor for TGF‐β1 levels in psoriasis (in this study, we selected most recent developing psoriatic plaques in the patient to examine); (c) different methods of detection of TGF‐β1 in these studies (d) detection of TGF‐β1 in scales is not the best accurate way for measurement of this protein 9 …”
Section: Discussionmentioning
confidence: 96%
“…Xenograft models of psoriasis, in which unaffected skin from psoriasis patients was grafted on immunodeficient mice, showed that stimulation with bacterial antigen could trigger the skin to become lesional (Boehncke et al 1996). Early culture-based studies examining microorganisms associated with psoriasis identified Malassezia, group A and B b-hemolytic streptococci, S. aureus, and Enterococcus faecalis (Aly et al 1976;Rosenberg et al 1994;Nickoloff et al 2000). Culture-independent analysis of fungal microbiota found no conclusive evidence to link Malassezia with psoriasis (Paulino et al 2006(Paulino et al , 2008.…”
Section: Psoriasismentioning
confidence: 99%